G244(P) "Blessing in Disguise": Noonan Syndrome with JMML. (7th April 2014) - Nazir, S; Baker, J; Thattakkat, K; Moppett, J
Abstract : Aims: Dr Jacqueline Noonan (1962) identified a cohort of patients with typical facial features, short stature, pulmonary artery narrowing and chest deformities. Subsequently they were recognised as having Noonan syndrome (NS); incidence of 1:1000 to 1:2500 live births. Recent advances in molecular genetics have identified considerable genetic heterogenicity within NS and at least six well defined genetic abnormalities (PTPN11, SOS1, RAF1, KRAS, NRAS, BRAF). 50% of cases show germline gain-of-function PTPN11 gene mutation predisposing to an increased risk of Juvenile Myelo Monocytic Leukaemia (JMML) that fortunately has very favourable prognosis in NS in comparison to non-syndromic JMML. We wish to illustrate this and share our recent clinical experience. Methods: We report a Neonate with Noonan Syndrome and JMML associated with germline PTPN11 mutation. The clinical course was studied and a systematic literature review was undertaken using search words "Noonan Syndrome" AND "JMML" OR "Juvenile Myelomonocytic Leukaemia" OR "Juvenile Myelomonocytic Leukaemia" AND "PTPN11 mutation". Results: A preterm infant was born to a lady with Noonan phenotype with antenatal suspicion of NS due to increased nuchal translucency on scans. Postnatally there was progressive increase in white cell count (maximally 57.6) with monocytosis (maximally 9.4)and splenomegaly within first few weeks of life; subsequently diagnosed as JMML morphologically. Further investigations identified PTPN11 mutation in both germline and leukaemic DNA. The infant was closely monitored clinically and haematologically. White cell count gradually normalised at 7 months of age, infant has no organomegaly and remains clinically well without specific treatment. Conclusion: Noonan syndrome, when associated with a germ line PTPN11 mutation, predisposes to a myelo-proliferative disorder phenotypically identical to JMML. Somatic gain-of-function mutations in PTPN11 have been found in 34% of non-syndromic JMML. The prognosis for JMML in Noonan syndrome is generally very good, with spontaneous resolution within the first year of life, whereas non-syndromic JMML normally requires allogeneic hematopoietic stem-cell transplant. Similar cases have previously been reported from Spain, Denmark and Germany but none from the UK to our knowledge. We wish to highlight awareness and recognition of this unique association that helps to confirm clinical diagnosis and to appropriately counsel parents regarding the good prognosis of this otherwise life-threatening disorder.